2016
DOI: 10.1177/0890334416646566
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Lead Levels in 3 Major Regions of the West Bank of Palestine

Abstract: Breast milk lead levels were higher than the safety limits for occupationally unexposed populations. Authorities need to implement measures to eliminate or reduce lead exposure, especially in refugee camps and cities. Marketed eye kohl preparations should be tested for their lead contents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…Arsenic exposure primarily occurs through drinking water or food, and naturally high groundwater levels of arsenic occur in several countries, including Argentina and the US [ 61 ]. Higher levels of lead in human milk have been reported in women that live closer to industrial [ 51 , 50 ] or urban areas [ 62 ], or use cosmetics containing lead [ 11 ]. However, risk factors for toxic metal exposure were not directly assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arsenic exposure primarily occurs through drinking water or food, and naturally high groundwater levels of arsenic occur in several countries, including Argentina and the US [ 61 ]. Higher levels of lead in human milk have been reported in women that live closer to industrial [ 51 , 50 ] or urban areas [ 62 ], or use cosmetics containing lead [ 11 ]. However, risk factors for toxic metal exposure were not directly assessed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…g . [ 11 , 12 , 36 , 48 ]). Further studies will be needed to add robust datasets from diverse populations to these new values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sources include water, air, and soil [6,12,13]. Increasing exposure to environmental lead has been attributed to recent industrialization and urbanization in some regions [13,14]. Recent studies have shown that plants and grains grown upon soils contaminated with lead contained elevated levels of this toxic heavy metal [10,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of lead contaminated hen eggs can increase lead levels in children and adults [10]. A recent study conducted on breastfeeding women from the West Bank of Palestine showed that about 19% of the breast milk samples analyzed contained lead levels above those recommended by the World Health Organization (WHO) [14]. Studies have found a link between higher lead levels and hypertension, renal failure, and depression [2,20,21].…”
Section: Introductionmentioning
confidence: 99%